Long-term performance of polymer concrete for bridge decks - Fowler, David W. (Synthesis of highway practice ;, 2011)
"TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 423: Long-Term Performance of Polymer Concrete for Bridge Decks addresses a number of topics related to thin polymer overlays (TPOs). Those topics include previous research, specifications, and procedures on TPOs; performance of TPOs based on field applications; the primary factors that influence TPO performance; current construction guidelines for TPOs related to surface preparation, mixing and placement, consolidation, finishing, and curing; repair procedures; factors that influence the performance of overlays, including life-cycle cost, benefits and costs, bridge deck condition, service life extension, and performance; and successes and failures of TPOs, including reasons for both."--Publisher's description.